Modeling Learning Patterns to Predict Placebo Analgesic Effects in Healthy and Chronic Orofacial Pain Participants - Wang, Yang; Tricou, Christina; Raghuraman, Nandini; Akintola, Titilola; Haycock, Nathaniel R.; Blasini, Maxie; Phillips, Jane; Zhu, Shijun; Colloca, Luana (Frontiers in Psychiatry, 2020)
Successfully predicting the susceptibility of individuals to placebo analgesics will aid in developing more effective pain medication and therapies, as well as aiding potential future clinical use of placebos. In pursuit of this goal, we analyzed healthy and chronic pain patients’ patterns of responsiveness during conditioning rounds and their links to conditioned placebo analgesia and the mediating effect of expectation on those responses. We recruited 579 participants (380 healthy, 199 with temporomandibular disorder (TMD)) to participate in a laboratory placebo experiment. Individual pain sensitivity dictated the temperatures used for high- and low-pain stimuli, paired with red or green screen displays, respectively, while participants were told there would be an analgesic intervention paired with green screens. Participants rated the painfulness of each stimulus on a visual analogue scale from 1-100. Delta scores, defined as each low-pain rating subtracted from its corresponding high-pain rating, served as means of modeling trajectories. During a testing phase, the same temperature was used regardless of visual stimulus, and individual placebo effect was defined as the difference between the average of the high-cued stimuli and low-cued stimuli. Latent Class Analysis was then conducted to cluster the participants based on the trajectories of the delta values of the conditioning rounds. Clusters characterized by persistently greater or increasing delta scores during the conditioning displayed greater placebo analgesia than those with persistently lower or decreasing delta scores. Furthermore, expectations tuned by the Clusters acted as a mediator for individual placebo analgesic effects. This study is the first to explore placebo analgesia in TMD and LCA as a means of discerning the relationship between the patterns of learning and the resulting placebo analgesia.